Experimental and Computational Analysis of Polyglutamine-Mediated Cytotoxicity - Tang, Matthew (Université d'Ottawa / University of Ottawa, 2012)
Expanded polyglutamine proteins are known to be the causative agents of a number of human neurodegenerative diseases but the molecular basis of their cytoxicity is still poorly understood. Polyglutamine tracts may impede the activity of the proteasome, and evidence from single cell imaging suggests that the sequestration of polyglutamine proteins into inclusion bodies can reduce the proteasomal burden and promote cell survival, at least in the short term. The presence of misfolded protein also leads to activation of stress kinases such as p38MAPK, which can be cytotoxic. The relationships of these systems are not well understood. We have used fluorescent reporter systems imaged in living cells, and stochastic computer modeling to explore the relationships of expanded polyglutamine proteins, p38MAPK activation, generation of reactive oxygen species (ROS), proteasome inhibition, and inclusion body formation. In cells expressing a polyglutamine protein, inclusion body formation was preceded by proteasome inhibition but cytotoxicity was greatly reduced by administration of a p38MAPK inhibitor. Computer simulations suggested that without the generation of ROS, the proteasome inhibition and activation of p38MAPK would have significantly reduced toxicity. Our data suggest a vicious cycle of stress kinase activation and proteasome inhibition that is ultimately lethal to cells. There was close agreement between experimental data and the predictions of a stochastic computer model, supporting a central role for proteasome inhibition and p38MAPK activation in inclusion body formation and ROS-mediated cell death.
Keywords: Polyglutamine; Huntington's disease; Spinocerebellar ataxia; Neurodegeneration; ubiquitin; proteasome; p38MAPK; Time lapse imaging